Sex‐based differences in apnoea of prematurity: A retrospective cohort study. Issue 10 (5th August 2018) - Bairam, Aida; Laflamme, Nathalie; Drolet, Christine; Piedboeuf, Bruno; Shah, Prakesh S.; Kinkead, Richard
Abstract : New Findings: What is the central question of the study? Is there a sex‐based difference in the incidence of apnoea of prematurity and the success or failure of caffeine therapy in preterm infants? What is the main finding and its importance? Our data show that females received fewer days of caffeine treatment than males. This was most noticeable in infants born between 26 0/7 and 27 6/7  weeks of gestational age. These results highlight the importance of considering sex in clinical and basic research investigating the pathophysiology of apnoea of prematurity. Abstract: This retrospective cohort study assessed whether sex influences the occurrence of apnoea of prematurity (AOP) in preterm infants. The analysis included a cohort of 24, 387 preterm infants born between the gestational ages (GA) of 24 0/7 and 33 6/7  weeks that were admitted to tertiary neonatal care units participating in the Canadian Neonatal Network from January 2011 to December 2015. Of those, 13, 983 (57%) were diagnosed with AOP. More females were diagnosed with AOP than males, but the difference in the male/female ratio was marginal ( P  = 0.058). The majority (89%) of infants diagnosed with AOP received caffeine (89% of males; 89% of females). By using the discontinuation of caffeine therapy as a proxy for the resolution of significant AOP, data analysis showed that females born before 33 6/7 weeks of GA stopped caffeine treatment earlier than males whether the caffeine was discontinued before 34 or 37 weeks of GA. Consequently, females had fewer days of caffeine therapy than males, especially infants born between 26 0/7 and 27 6/7  weeks ( P  < 0.004), 28 0/7 and 29 6/7  weeks ( P  < 0.03), and 32 0/7 and 33 6/7  weeks of GA ( P  < 0.04). Similar trends were observed when the corrected GA at discontinuation of caffeine was used. Given that AOP is indicative of an immature respiratory system, our data suggest that the maturation of the respiratory system might occur more rapidly in females than males. We conclude that sex needs to be considered in future studies on AOP. Abstract :